2005
DOI: 10.1007/s11243-005-6275-5
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for the Preparation of Tetra-Coordinate Platinum(II) Chloro-Complexes Containing Bidentate or Terdentate Ligands Starting from cis/trans-[PtCl2(SMe2)2]

Abstract: An improved method for the preparation of differently charged chelate Pt(II) chloro-complexes is reported. All the complexes have been obtained rapidly and in high yield, by simply reacting equimolar amounts of cis/transdichlorobis(dimethylsulphide)platinum(II) with the chelate ligand in an appropriate solvent (CH 2 Cl 2 , MeOH or H 2 O). The ligands chosen were: 1,2-bis(diphenylphosphino)ethane (PAP), pyridine-2-carboxylate (NAO ) ), 2-[(methylthio)methyl]pyridine (NAS), 1,10-phenanthroline (NAN), bis(2-pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…11 Calculations were performed at the B3LYP level of theory using LANL2DZ as the basis set for Pt and 6-31G* for all other atoms. 12 Syntheses of p-(dimesitylboryl)phenylacetylene, 13 Pt(dbbpy)Cl 2 (dbbpy = 4,4 0 -di-tert-butyl-2,2 0 -bipyridine), 14 Pt(dppp)Cl 2 (dppp = 1,3-diphenylphosphinopropane), 15 and Pt(dbbpy)(CtCC 6 H 5 ) 2…”
Section: ' Experimental Sectionmentioning
confidence: 99%
“…11 Calculations were performed at the B3LYP level of theory using LANL2DZ as the basis set for Pt and 6-31G* for all other atoms. 12 Syntheses of p-(dimesitylboryl)phenylacetylene, 13 Pt(dbbpy)Cl 2 (dbbpy = 4,4 0 -di-tert-butyl-2,2 0 -bipyridine), 14 Pt(dppp)Cl 2 (dppp = 1,3-diphenylphosphinopropane), 15 and Pt(dbbpy)(CtCC 6 H 5 ) 2…”
Section: ' Experimental Sectionmentioning
confidence: 99%
“…The ability of the transition metal precursor to coordinate the 8-aminoquinoline and the other N-heterocycle is, instead, of primary importance. The metal-assisted condensation does not happen, for example, using PtCl 2 (COD), which is less reactive than cis/trans-PtCl 2 (SMe) 2 [23]. Moreover, in our previous studies we have observed in some cases that the metal-assisted condensation happens only by removing a coordinated chloroligand from the transition metal precursor using a silver salt [10].…”
Section: Factors Influencing the Reaction Mechanismmentioning
confidence: 97%
“…Chloro-complexes of Pt(II) and Pd(II) containing a pyridine ring in the tridentate ligand have been already prepared on the basis of the same synthetic approach [10]. Preliminary studies have shown that the complex PtCl 2 (COD) is not a suitable precursor for the metal-assisted condensations considered in this work, having a lower reactivity as compared to cis/trans-PtCl 2 (SMe 2 ) 2 [23]. The formation of tridentate cationic complexes has been confirmed by their elemental analyses (C, H, N, Cl), the conductivity of their solutions in polar solvents and their NMR spectra.…”
Section: Characterization Of 9 Nnthmentioning
confidence: 99%